2022
DOI: 10.1155/2022/7302240
|View full text |Cite
|
Sign up to set email alerts
|

Daily Activity Pattern of Geladas (Theropithecus gelada, Ruppell 1835) in Kotu Forest, Northern Ethiopia

Abstract: Gelada (Theropithecus gelada) is one of the endemic primates of Ethiopia. The ecology of meta populations of geladas outside protected areas is less studied, and their population status is uncertain. As a result, we conducted a study to investigate the daily activity pattern of gelada in Kotu forest and associated grasslands in northern Ethiopia from August 2017 to February 2018 covering both wet and dry seasons. The instantaneous scan sampling method was employed to collect behavioral data. The activity patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
4
4
0
Order By: Relevance
“…The possible reason could be that during the dry season, su cient amounts of food and water were not readily available at Cliff/Rocky habitat. In line with the present study, [45] reported geladas were observed to move long distances in search of green fresh leaves outside the study area in the dry season, while they did not go far from their cliffs during the wet season due to that gelada spent more time at cliff habitat.…”
Section: Habitat Utilization Of Gelada Monkeyssupporting
confidence: 91%
See 3 more Smart Citations
“…The possible reason could be that during the dry season, su cient amounts of food and water were not readily available at Cliff/Rocky habitat. In line with the present study, [45] reported geladas were observed to move long distances in search of green fresh leaves outside the study area in the dry season, while they did not go far from their cliffs during the wet season due to that gelada spent more time at cliff habitat.…”
Section: Habitat Utilization Of Gelada Monkeyssupporting
confidence: 91%
“…In the present study, (54.52%) of geladas spent more time feeding than other activities, similar to the previous ndings at Wonchit Valley [36], Zlin-Lesna Zoo [42], Simien Mountains National Park [43], Debre-Libanos Monastery Forest [44], South Rift Valley of Ethiopia [35], Abogedam Church West of Debre Berhan Town [22] and Kotu Forest [45] discovered that geladas spent more time to feeding than other activities. The cause for a high proportion of time dedicated to the feeding activity may be due to the food which may have lower nutritional quality [46], and better habitat quality is associated with decreased feeding and increased resting among gelada groups.…”
Section: Activity Time Budgetsupporting
confidence: 91%
See 2 more Smart Citations
“…Due to different anthropogenic factors including habitat fragmentation, metapopulations of geladas were created and such populations are widely separated apart, inhabiting areas that are inaccessible and unprotected. As a result, metapopulations of geladas over many fragmented areas remain largely unstudied (Degu & Zerihun, 2022). A number of studies on the daily activity patterns and feeding ecology of geladas in Ethiopia over protected areas have been conducted.…”
Section: Introductionmentioning
confidence: 99%